Functional macroporous iron-phosphorous films by electrodeposition on colloidal crystal templates. (1st August 2019) - Golvano-Escobal, Irati; de Paz-Castany, Roger; Alcantara, Carlos C.J.; Pané, Salvador; García-Lecina, Eva; Sort, Jordi; Pellicer, Eva
Abstract: Pseudo-ordered macroporous iron-phosphorous (Fe-P) films have been electrodeposited potentiostatically from a citrate-sulfate bath onto Au surfaces pre-patterned with a colloidal crystal mask of polystyrene spheres of 350 nm in diameter. The electrolyte contained sodium hypophosphite as the P source, enabling the incorporation of 6–14 at.% P. For comparative purposes, continuous films have been obtained galvanostatically on unpatterned Au surfaces. In both cases, the P content could be varied to a certain extent by adjusting the deposition potential or current density. Tunable microstructure and magnetic response was observed due to the dissimilar chemical composition, with coercivity values being larger in the macroporous films. Additionally, wettability analyses showed that these were more hydrophobic, reaching contact angle values of about 130 ∘ . In spite of their hydrophobic character, the samples were catalytic toward oxygen evolution reaction (OER) in alkaline media. The macroporous Fe-P films showed faster kinetics for OER than their nonporous counterparts. Our results show that electrodeposited porous Fe-P based materials show an interesting combination of properties which make them appealing for applications including water cleaning, soft-magnetic components, or electrocatalytic production of oxygen, to name a few. Graphical abstract: Image 1